Barriers and Enablers for Adherence to Antiretroviral Therapy Among People Living With HIV/AIDS in the Era of COVID-19: A Qualitative Study From Pakistan - Ahmed, Ali; Dujaili, Juman Abdulelah; Jabeen, Musarat; Umair, Malik Muhammad; Chuah, Lay-Hong; Hashmi, Furqan Khurshid; Awaisu, Ahmed; Chaiyakunapruk, Nathorn (Frontiers in Pharmacology, 2022)
Background: With the increased availability of safe antiretroviral therapy (ART) in recent years, achieving optimal adherence and patient retention is becoming the biggest challenge for people living with HIV (PLWH). Care retention is influenced by several socioeconomic, socio-cultural, and government policies during the COVID-19 pandemic. Therefore, we aim to explore barriers and facilitators to adherence to ART among PLWH in Pakistan in general and COVID-19 pandemic related in particular. Methods: Semi-structured interviews were conducted among 25 PLWH from December 2020 to April 2021 in the local language (Urdu) at the ART centre of Pakistan Institute of Medical Sciences, Islamabad, Pakistan. Interviews were audio-recorded in the local Urdu language, and bilingual expert (English, Urdu) transcribed verbatim, coded for themes and sub-themes, and analyzed using a phenomenological approach for thematic content analysis. Results: Stigma and discrimination, fear of HIV disclosure, economic constraints, forgetfulness, religion (Ramadan, spiritual healing), adverse drug reactions, lack of social support, alternative therapies, and COVID-19-related lock-down and fear of lesser COVID-19 care due to HIV associated stigma were identified as barriers affecting the retention in HIV care. At the same time, positive social support, family responsibilities, use of reminders, the beneficial impact of ART, and initiation of telephone consultations, courier delivery, and long-term delivery of antiretrovirals during COVID-19 were identified as facilitators of HIV retention. Conclusion: Improving adherence and retention is even more challenging due to COVID-19; therefore, it requires the integration of enhanced access to treatment with improved employment and social support. HIV care providers must understand these reported factors comprehensively and treat patients accordingly to ensure the continuum of HIV care. A coordinated approach including different stakeholders is required to facilitate patient retention in HIV care and consequently improve the clinical outcomes of PLWH.